Comparative genomics analyses of alpha-keratins reveal insights into evolutionary adaptation of marine mammals - Xiaohui Sun; Zepeng Zhang; Yingying Sun; Jing Li; Shixia Xu; Guang Yang (Frontiers in Zoology, 2017)
Abstract Background Diversity of hair in marine mammals was suggested as an evolutionary innovation to adapt aquatic environment, yet its genetic basis remained poorly explored. We scanned α-keratin genes, one major structural components of hair, in 16 genomes of mammalian species, including seven cetaceans, two pinnipeds, polar bear, manatee and five terrestrial species. Results Extensive gene loss and high pseudogenization rate of α-keratin genes were identified in cetaceans when compared to terrestrial artiodactylans (average number of α-keratins 37.29 vs. 58.33; pseudogenization rate 29.89% vs. 8.00%), especially of hair follicle-specific keratin genes (average pseudogenization rate in cetaceans of 43.88% relative to 3.80% artiodactylian average). Compared to toothed whale, the much more number of intact functional α-keratin genes was examined in the baleen whale that had specific keratinized baleen. In contrast, the number of keratin genes in pinnipeds, polar bear and manatee were comparable to those of their respective terrestrial relatives. Additionally, four keratin genes (K39, K9, K42, and K74) were found to be pseudogenes or lost uniquely in cetaceans and manatees. Conclusions Species-specific evolution of α-keratin gene family identified in the marine mammals might be responsible for their different hair characteristics. Increased gene loss and pseudogenization rate identified in cetacean lineages was likely to contribute to hair-less phenotype to adaptation for complete aquatic environment. However, the fully aquatic manatee still remained the comparable number of intact genes to its terrestrial relative, probably due to its perioral bristles and bristle-like hairs on the oral disk. By contrast, similar evolution pattern of α-keratin gene repertoire in the pinnipeds, polar bear and their terrestrial relatives was likely due to abundant hair to keep warm when they went ashore. Interestingly, some keratin genes were exclusively lost in cetaceans and manatees, likely as a result of convergent hair-loss phenotype to inhabit completely aquatic environment in both groups.